Measuring the impact of influenza vaccination programmes among the elderly population in Spain, the Netherlands and Portugal, 2015-2018 - Mazagatos, Clara (2020)
Measuring the number of influenza-associated events prevented by influenza vaccination among the elderly in the European Union would allow a better understanding of the overall impact of influenza vaccination programmes, particularly in seasons with low influenza vaccine effectiveness (IVE). This study measured the number of medically attended influenza-confirmed cases in primary care (MAICC) among those ≥65 years averted by influenza vaccination programmes in Spain (SP), the Netherlands (NL) and Portugal (PT), from 2015 to 2018.